Development Of Classical Guidance Media Using Virtual Reality (VR) Technology To Build Student Resilience In Earthquake-Prone Areas - Ira Oktarini (International Journal of Technology and Education Research, 2026)
Guidance classical as service preventive measures in schools in vulnerable areas earthquake earth For build resilience is very necessary For realized, but its implementation Still hampered by the limitations of conventional media which do not capable provide experience Study immersive and realistic related situation earthquake Earth. Research This aim For construct runway theoretical and conceptual for development of guidance media classical using Virtual Reality (VR) technology which is specific designed For build resilience students in vulnerable areas earthquake earth. Type research used is studies library or library research with data sources in the form of books, articles journal scientific, and reports results research. Research results show four findings main. First, students in disaster prone areas earthquake earth own need complex psychology covering need for security, regulation emotion, efficacy self, support social, and meaning positive, all of which is component former resilience. Second, guidance classical effective as a preventive strategy For build resilience if designed with approach experiential and multi-modal. Third, VR technology has potential wide application in guidance and counseling, especially through his abilities present simulation earthquake an immersive, safe, and controlled earth For therapy exposure, training skills, and psychoeducation interactive. Fourth, synthesis third findings the produce framework conceptual integrated media development theory resilience, learning experiential, and presence theory in VR, with notice principle design instructional, gamification, adaptation cultural, as well as activity reflective pre and post VR Implementation results study realized through development VR media prototype with scenario simulation earthquake multi- storey equipped guide facilitation, sheet reflection, and instruments assessment resilience contextualized.